Contemporary Capacity-Building in Educational Contexts - Danaher, Patrick Alan.; Davies, Andy.; George-Walker, Linda De.; Jones, Janice K.; Matthews, Karl J.; Midgley, Warren; Arden, Catherine H.; Baguley, Margaret; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2014)
Education is generally supposed to help learners to develop new capacities and to be able to apply them in work and life - yet we still know very little about how to build useful capacities. This book investigates nine research projects, exploring why particular capacities are successful in some situations but not in others.
Keywords: Science; Science; Science, general